Address of the Chairman of the Supreme Eurasian Economic Council, President of the Russian Federation Vladimir Putin to the Heads of the EAEU Member States on the Occasion of Russia's Chairmanship in the Bodies of the Union in 2023 - article Editorial (Евразийская интеграция: экономика, право, политика, 2023)
.